(3ShGFM GdbQjMI aj TQM GdUajMIs - (3CHh eMeO YHO Gddg Hf aNQ GdOjf GdCYQL GdMSjfj GdehUdj GdMfaj GdeYQha HaNQi RGOgs; (3HgGA GdOjf eMeO Hf MSjf GdMGQKj GdgeOGfj GdTjYj GdYGedj,J (B1031 (3g` s
(3ChdgG (B:s
(3JHGQc GdPi LYd ai GdSeGA HQhLkG hHYO , ajbhd HgGA GdOjf eMeO GdYGedi gPg QSGdI UZjQI GdMLe eSejkG dgG HGdUajMI hcPdc jbhd CHh eMeO YHO Gddg Hf aNQ GdOjf GdMSjfi GdehUdi s
(3BNQgG (B:s
(3hGdeUdi EPG LYdg Hjf bOjeg hSLO Ydjg eJhLgkG Edi CUd GdebjGS jchf ehGLgkG ddbHdI bGd hdjcf gPG BNQ eG CQOfG EjQGOg ai gPg GdChQGb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B2s
(3HgG fXGe GdJYbjHIs
(3ai GdCSWQdGHs
(3cJHJ Hbde ajg VHWs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs